West Papua ‘independence’ and the Papua New Guinea press - Patrick Matbob; Evangelia Papoutsaki (Pacific Journalism Review, 2006)
This article explores the West Papua issue through the Papua New Guinea news media. It seeks to identify the reasons behind the decline in coverage of West Papua in the PNG press. It provides an historical background to the West Papua conflict and PNG’s relationship with Indonesian-ruled West Papua and it presents the results of a comparative content analysis of three PNG newspapers—Post-Courier, The National, and Times of Papua New Guinea—on their coverage of West Papua, in-depth interviews with journalists and West Papuan refugees in Papua New Guinea.